Ethnobotanical Survey of Woody Plants in Shorobe and Xobe Villages, Northwest Region of Botswana - Neelo, John; Kashe, Keotshephile; Teketay, Demel; Masamba, Wellington (Ethnobotany Research and Applications, 2015)
Ethnobotanical investigations were conducted at Xobe and Shorobe Villages in northwestern Botswana to identify woody plants used by the local people. A total of 90 households (35 in Xobe and 55 in Shorobe) were interviewed using a semi-structured questionnaire and personal interviews. A total of 38 woody species representing 16 families and 25 genera were recorded. Of these, 28 species representing 15 families and 22 genera were recorded from Shorobe, and 27 species representing 10 families and 15 genera were recorded from Xobe. The uses of woody plants were grouped into eight categories, namely construction, fuelwood, furniture, medicine, human food, fodder, farm implements, and shade. Several of the species are used for more than one purpose. At both study sites, the use category with the highest proportion of number of woody species and proportion among the use categories was human food. Thirteen of the families were represented by 23 woody species that are used for medicinal purposes, and the most commonly used plant parts were the roots, bark, leaves, and stems. Nine of the 28 woody species (28%) in Shorobe and nine of the 27 woody species (33.3%) in Xobe provide edible parts. Six (21%) and eight (30%) woody species recorded in Shorobe and Xobe, respectively, are used for construction purposes. Most plants are used as fuelwood for household energy generation. In spite of the scarcity of natural forests in the study areas, the local communities continue to depend on the indigenous woody species in their surroundings for their survival. Virtually all trees identified in the different families are useful in one way or another in the lives of the rural communities, with most of the species serving more than one function. There is, therefore, a need for cultivation, protection, and sustainable management of these valuable resources for sustaining rural livelihoods in the study sites.